Endoscopic Management with a Novel Over-The-Scope Padlock Clip System - Mahesh Kumar Goenka; Gajanan Ashokrao Rodge; Indrajeet Kumar Tiwary (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims: The Padlock clip is a recently introduced over-the-scope clip (OTSC) that requires the use of an alternate technique and has a different design from previous OTSCs. However, data regarding its clinical use are limited. The aim of this study is to present our clinical experience using this novel Padlock clip system. Methods: Between September 2018 and June 2019, 7 consecutive patients underwent Padlock clip application at our center by an experienced endoscopist. A Padlock clip was used for achieving hemostasis in 4 patients presenting with gastrointestinal (GI) bleeding, as well as for endoscopic full-thickness resection in the remaining 3 patients. Results: All 7 patients achieved technical as well as clinical success, with absence of complications or rebleeding, during a follow-up of a minimum of 3 weeks. All patients were hospitalized post procedure for a minimum of 48 hours, and an absence of adverse events was noted in our patient population throughout the procedure and post-procedure period. Antiplatelet therapy was reinstated shortly after the application of the Padlock clip, with no GI bleeding observed. Conclusions: The Padlock clip is a novel OTSC, with benefits that include safe, simple, and rapid deployment. Antiplatelet therapy may be reinstated for patients, when necessary, shortly after applying the Padlock clip due to full-thickness closure of the tissue.